Proyecto de factibilidad para la creación de un centro automotriz express en la ciudad de Loja. - SÁNCHEZ LOZANO, SANTIAGO GREGORIO (2012)
The present research aims to develop an overall project feasibility for the implementation of a maintenance company express light vehicles in the city of Loja, to provide quality care in a timely and efficient, thus offering a option to the community as far as this business is concerned. According to data obtained in 2011 the population of 25,231 vehicles would be investigated that are circulating in the city of Loja, of which 87.44% were bone light vehicles 22,061 light vehicles, with this tool, we calculated the number of survey to be applied with a total of 393 surveys, this allowed us to know the future behavior of market price, demand, trade, which is essential for preinvestment analysis. According to statistical data in the study of effective demand determined market is contained in 66,444 light vehicles and with an offer of 26,400 vehicles which get an unmet demand for 40,044 vehicles. Then he proceeded to raise the technical study, here we determine the installed capacity will reach 17,520 this capacity to cover 44% of unmet demand, capacity utilization is 3960 use the services reaching 23% of installed capacity in this first year of life service. The location of the company will be in the industrial park of Loja to meet the standards of beautification and avoid problems in the future, project engineering function is to couple the physical resources for optimum production requirements in the construction and business equipment. What gives the automaker is a joint service of ABC engine, ABC brakes and oil change. The financial study of the project we consider all the items needed to determine the investment required for implementation, production costs for the projected budget for the 10 year life of the project shall be discussed as important points: the selling price the public that is $ 55.00 per service, the equilibrium point for the first year has determined that the company must work to 25% of installed capacity and have a sales income of $ 54,477 dollars in the first year for the company not lose or win. The indicators accepted in the evaluation of the project are the net present value of the project (NPV) is $ 332.232.03 dollars, the internal rate of return (IRR) that we as a percentage of 50.54% higher than the minimum required by the investor, a cost / benefit ratio of 1.81, we also get a payback period of capital that is 2 years, 11 months and 5 days, before the project ends its life, which makes it safe, the sensitivity analysis determines that the project would support costs increased 15% and a decrease in revenues of 10%. Having had a thorough investigation for the development of the feasibility project for the creation of an express auto center in the city of Loja, we proceed to make findings and recommendations.